Naturido alleviates amyloid β1–42-induced adverse effects in a transgenic Caenorhabditis elegans model of Alzheimer’s disease - Piyamas Sillapakong; Tokumitsu Wakabayashi; Koichi Suzuki (PLoS ONE, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder primarily associated with aging. While the amyloid hypothesis is not the only explanation for AD pathogenesis, it is widely recognized that the accumulation of amyloid β (Aβ) protein triggers pathological changes in the brains of patients. In a previous study, we showed that Naturido, a cyclic peptide derived from the medicinal fungus (Isaria japonica) grown on domestic silkworms (Bombyx mori), could reverse several age-related deficits in senescence-accelerated mice. In this study, we explored the potential of Naturido to reduce Aβ-related toxicity in transgenic Caenorhabditis elegans models of AD, where human Aβ1-42 protein is overexpressed in neurons. Our results demonstrated that Naturido administration alleviated various phenotypes, including Aβ-induced impairment in associative learning, serotonin hypersensitivity, and locomotion in the transgenic C. elegans. These findings suggest the potential of Naturido as a candidate molecule for the prevention and/or treatment of AD.